Integrated weed control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The Economic European Community (EEC) is backing a joint venture of the French CIRAD (1) and the Tropical Weed Group's Research Division at Bristol in Great Britain in order to launch a two-year integrated weed control project in developing...